2018
DOI: 10.1097/md.0000000000011647
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular invasion can be better than pathologic complete response to predict prognosis in breast cancer treated with neoadjuvant chemotherapy

Abstract: Lymphovascular invasion (LVI) has been a predictor of worse survival outcomes in breast cancer. However, the role of LVI compared than pathologic complete response (pCR) following neoadjuvant chemotherapy (NAC) remains unclear. The aim of this study was to examine the association between LVI and survival outcomes and clinicopathological features in patients with breast cancer treated with NAC. We retrospectively analyzed 187 patients with breast cancer treated with NAC and surgery between 2005 and 2013 in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 30 publications
6
36
0
7
Order By: Relevance
“…However, the relation was non-significant in the adjuvant group. In the study by Ryu et al, 14 out of 187 patients, 35% patients showed LVI. The LVI group tended to have advanced status in terms of disease burden (clinical stage III) and had statistical significance.…”
Section: Lymphovascular Invasionmentioning
confidence: 89%
“…However, the relation was non-significant in the adjuvant group. In the study by Ryu et al, 14 out of 187 patients, 35% patients showed LVI. The LVI group tended to have advanced status in terms of disease burden (clinical stage III) and had statistical significance.…”
Section: Lymphovascular Invasionmentioning
confidence: 89%
“…The most relevant factors for LRC and DFS were LVI and close resection margins in multivariate analysis. The association between the presence of LVI after NAC and poor prognosis has been demonstrated in several other studies [171819]. Close resection margins have been reported to be present in 6.1%–12.5% of patients following mastectomy [2021].…”
Section: Discussionmentioning
confidence: 79%
“…Two studies conducted in South Korea reported the relationship between LVSI and poor prognosis of both operable invasive breast cancer and breast cancer treated with neoadjuvant chemotherapy. 31,32 LVSI as a predictor of node metastases²⁷ and prognostic factor of breast cancer 31,32 also has been reported. Their results were similar with our study that showed 47.7% of patients with breast cancer had positive LVSI, and 86.3% of them had ALN involvement.…”
Section: Resultsmentioning
confidence: 92%